What is the result when 2x3 - 9x2 + 11x - 6 is divided by x - 3?
Solution:
A polynomial is a type of expression in which the exponents of all variables should be a whole number.
Given: Dividend = 2x3 - 9x2 + 11x - 6, Divisor = x - 3
We will use the long division of polynomials to divide the two polynomials
Let's look into the division shown below:
Thus, we see that the quotient is 2x2 - 3x + 2
The Division algorithm for polynomials says if p(x) and g(x) are the two polynomials, where g(x) ≠ 0, we can write the division of polynomials as:
p(x) = q(x) × g(x) + r(x) ---------------- (1)
Where,
Verification:
p(x) = 2x3 - 9x2 + 11x - 6, g(x) = x - 3, q(x) = 2x2 - 3x + 2, r(x) = 0
Substituting the values in RHS of (1) we get,
RHS = q(x) × g(x) + r(x)
RHS = (x - 3) (2x2 - 3x + 2)
RHS = 2x3 - 9x2 + 11x - 6 = p(x)
Thus, we see that LHS = RHS
We can also use Cuemath's online polynomial calculator to perform different arithmetic operations on polynomials.
Hence, when 2x3 - 9x2 + 11x - 6 is divided by x - 3 we get 2x2 - 3x + 2.
What is the result when 2x3 - 9x2 + 11x - 6 is divided by x - 3?
Summary:
The result when 2x3 - 9x2 + 11x - 6 is divided by x - 3 is equal to 2x2 - 3x + 2.
visual curriculum